2006
DOI: 10.1111/j.1532-950x.2006.00179.x
|View full text |Cite
|
Sign up to set email alerts
|

A Clinical Evaluation of Pancarpal Arthrodesis in Nine Dogs Using Circular External Skeletal Fixation

Abstract: Pancarpal arthrodesis by use of CESF is a clinically applicable technique and may offer advantages over internal fixation with respect to postoperative complications.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
19
0
1

Year Published

2009
2009
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 13 publications
0
19
0
1
Order By: Relevance
“…External coaptation is not without the potential for inherent minor or major complications 3,14,15 and when used requires meticulous management by, and a further financial commitment from, the client in the postoperative period. 16 In a review of 11 ischemic bandage injuries, 5 resulted from application of a bandage or splint for injuries distal to the elbow. 15 Morbidity associated with external coaptation after partial carpal arthrodesis was reported in 35% of procedures.…”
Section: Advantages Of the Clpmentioning
confidence: 99%
See 1 more Smart Citation
“…External coaptation is not without the potential for inherent minor or major complications 3,14,15 and when used requires meticulous management by, and a further financial commitment from, the client in the postoperative period. 16 In a review of 11 ischemic bandage injuries, 5 resulted from application of a bandage or splint for injuries distal to the elbow. 15 Morbidity associated with external coaptation after partial carpal arthrodesis was reported in 35% of procedures.…”
Section: Advantages Of the Clpmentioning
confidence: 99%
“…The CLP manufacturer has proposed that improved mechanical characteristics circumvent the requirement for postoperative external coaptation. External coaptation is not without the potential for inherent minor or major complications 3,14,15 and when used requires meticulous management by, and a further financial commitment from, the client in the postoperative period 16 . In a review of 11 ischemic bandage injuries, 5 resulted from application of a bandage or splint for injuries distal to the elbow 15 .…”
mentioning
confidence: 99%
“…Pancarpal arthrodesis (PCA) in dogs and cats is used as a salvage procedure for treatment of end‐stage carpal conditions such as hyperextension, degenerative joint disease, congenital malformations and fractures, and luxations where conservative management has failed or is inappropriate. Surgical techniques used to achieve carpal arthrodesis include application of a plate to the dorsal, medial or palmar surfaces, or external skeletal fixation, with or without crossed K‐wires …”
mentioning
confidence: 99%
“…Arthrodesis techniques differ in technical difficulty and outcome. Currently, the most commonly performed treatment involves a dorsally applied plate with screws …”
mentioning
confidence: 99%
“…Other modifications such as combining crossed K‐wires with a dorsally applied bone plate has been postulated to negate the need for casting; this is supported by biomechanical studies that have shown a significantly higher yield failure when compared with a plate alone . As an alternative to plating, external skeletal fixators, both linear and circular, can be successfully used for carpal arthrodesis and compare favorably to dynamic compression plates (DCP) in mechanical testing and clinical outcome . On balance, however, dorsal plating has remained popular because of its relatively straightforward surgical approach, ability to apply compression across the arthrodesis, acceptable complication rates with perceived good outcomes, and familiarity with the technique.…”
mentioning
confidence: 99%